2016
DOI: 10.1155/2016/2359437
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Pulmonary Toxicity Associated with Brentuximab in a Patient with Refractory Hodgkin’s Lymphoma

Abstract: Acute pulmonary toxicity associated with brentuximab appears to be a rare but serious adverse effect that can be potentially fatal. We report the case of a twenty-nine-year-old female with Hodgkin's lymphoma who was treated with brentuximab and later presented with severe acute pulmonary toxicity; she improved after the discontinuation of brentuximab and administration of antibiotics and glucocorticoid therapy. Currently there is very little data in the literature in regard to the clinical manifestations and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
(16 reference statements)
2
13
0
Order By: Relevance
“…Pneumocystis pneumonia (PcP) was rare (0.1−1%) [14]. Noninfectious pulmonary toxicity has been reported [25], but is more likely to be attributable to the coadministration of bleomycin, so that this combination has become contra-indicated [9]. Large phase 3 studies did not show pulmonary toxicity when BV was not combined with bleomycin [21, 23].…”
Section: Immunotherapeutic Agents (Blinatumomab Brentuximab Vedotinmentioning
confidence: 99%
“…Pneumocystis pneumonia (PcP) was rare (0.1−1%) [14]. Noninfectious pulmonary toxicity has been reported [25], but is more likely to be attributable to the coadministration of bleomycin, so that this combination has become contra-indicated [9]. Large phase 3 studies did not show pulmonary toxicity when BV was not combined with bleomycin [21, 23].…”
Section: Immunotherapeutic Agents (Blinatumomab Brentuximab Vedotinmentioning
confidence: 99%
“…Other commonly observed non-hematologic toxicities were nausea, fatigue, diarrhea, pyrexia, rash, or upper respiratory infection. As pulmonary toxicities can occur in conjunction with concurrent or prior bleomycin use [ 72 93 ], the concomitant use of BV with bleomycin is contraindicated. Several reports indicated that BV treatment may induce the reactivation of polyomavirus JC, which can cause fatal progressive multifocal leukoencephalopathy [ 94 95 96 ].…”
Section: Clinical Datamentioning
confidence: 99%
“…In both studies, brentuximab vedotin was associated with high response rates and promising progression-free survival (PFS) and overall survival (OS), along with a number of important safety signals including peripheral neuropathy, infections, neutropenia, and infusion reactions [ 3 6 ]. Additionally, acute pulmonary toxicity is a rare adverse event (AE) associated with brentuximab vedotin use that is potentially life-threatening [ 7 ].…”
Section: Introductionmentioning
confidence: 99%